The Importance of a Proper Selection Area to be Biopsied in Nodular Leukoplakia: a Case Report - Otávio Pagin; Paulo Sérgio da Silva Santos; Nathalia Bigelli Del Neri; Heliton Gustavo de Lima; Vanessa Soares Lara (Acta Stomatologica Croatica, 2014)
Nodular leukoplakia is a non-homogeneous type of oral leukoplakia presenting a white surface with verrucous, nodular, ulcerated or erythematous features with a greater risk of malignant transformation when compared to the homogeneous type. Common sites of involvement include lip commissures, buccal mucosa and soft palate. It is often associated with epithelial dysplasia or carcinoma and requires detailed microscopic assessment and regular follow-up. The importance of a proper selection of the area to be biopsied and the close teamwork between a dentist and oral pathologist is the basis of providing an accurate final diagnosis.